Knowledge of the Nursing Team on the Blood Transfusion Process: Integrative Literature Review (Research, Society and Development, 2021)
Objective: To identify scientific studies on the knowledge of the nursing team in the face of a blood transfusion; observe the degree of knowledge of the nursing team regarding blood transfusion; identify the risk management tools that can contribute to this knowledge. Methodology: It is an Integrative Literature Review, exploratory with a qualitative approach on the knowledge of the nursing team on blood transfusion, carried out in national databases, in the period from 2015 to 2020. Result: Five articles were selected to analyze, evaluate, verify and investigate the knowledge (theory) of the nursing team, in blood transfusion; two studies sought to develop and describe educational technologies aimed at teaching nursing in assisting the blood transfusion process, of these one study described the process of construction and content validation of a checklist for blood transfusion in children, and the other developed an Instrument for monitoring of the patient undergoing blood transfusion.From the results found, four thematic categories were formed: The moment of pre-transfusion: initial gold step; The moment of transfusion; The moment of post-transfusion: it is not yet the end and the risk management tools in blood transfusion. Conclusion: We emphasize that although the nursing team reports having safety in the stages, it is contradictory to the data provided in the studies with the incipience of the knowledge of the nursing team in blood transfusion; these data answer the research question and corroborate the objectives of this study.